2002
DOI: 10.1002/adfm.200290008
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Tunneling Processes along Conjugated Molecular Wires: A Quantum‐Chemical Description

Abstract: Molecular electronics research is a very active area in the field of nanotechnology. It is now well established that individual or self‐assembled molecules can behave as nanoscopic switches in transistor and diode configurations. Molecular wires inserted into nanopores and contacted by two metallic electrodes can also be used as active elements for the fabrication of resonant tunneling diodes (RTDs). The RTD current/voltage (I/V) characteristics can display a negative differential resistance (NDR) behavior (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(40 reference statements)
1
5
0
1
Order By: Relevance
“…Note that either the hole or electron second resonance should be responsible for the sharp NDR behaviour, depending on the efficiency of their charge injection processes, which is directly related to the energy separation between the electronic levels and the Fermi energy of the gold surface. Further calculations have verified that the same resonant levels for electrons and holes can still be detected for torsion angles of the central ring in between 45 • and 90 • [11], thus validating the applicability of the same NDR mechanism. However, the enhanced delocalization of the molecular levels observed when deviating from a perpendicular conformation should contribute to a leakage current at low voltage, and hence to a reduced peak-to-valley ratio of the NDR signal.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Note that either the hole or electron second resonance should be responsible for the sharp NDR behaviour, depending on the efficiency of their charge injection processes, which is directly related to the energy separation between the electronic levels and the Fermi energy of the gold surface. Further calculations have verified that the same resonant levels for electrons and holes can still be detected for torsion angles of the central ring in between 45 • and 90 • [11], thus validating the applicability of the same NDR mechanism. However, the enhanced delocalization of the molecular levels observed when deviating from a perpendicular conformation should contribute to a leakage current at low voltage, and hence to a reduced peak-to-valley ratio of the NDR signal.…”
Section: Resultssupporting
confidence: 59%
“…The key idea of this mechanism, established under the assumption that charges have sufficient time to relax geometrically over the conjugated backbone, is that charge carriers can flow across a molecular junction if they are injected in a molecular level fully delocalized over the whole molecular backbone. However, the shape of the LUMO wavefunction is very sensitive to the choice of the quantum chemical approach used since the subtle localization versus delocalization effects are not reproduced by other theoretical approaches [11]; this suggests that the doping model might not be the actual mechanism leading to the NDR behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…As in other studies [23,24], we find that in bicycle bridges, the twisting angle between the two cycles controls the delocalization and the energy of the HOMO. At equilibrium geometry, the two cycles in the biphenyl bridge S-C 6 H 4 -C 6 H 4 -S are oriented at 32°.…”
Section: Ab Initio Computationsmentioning
confidence: 58%
“…In S-C 6 H 4 -C 2 -C 6 H 4 -S, the bridge is planar in the equilibrium geometry. In the triphenylethylene bridge, the negative differential resistance has been attributed to the twisting angle of the middle phenyl with respect to the two end phenyls, which was found to be of the order of kT [24]. Here, we found that the effect of twisting the two phenyl groups in the S-C 6 H 4 -C 2 -C 6 H 4 -S bridge is to increase the energy of the HOMO.…”
Section: Ab Initio Computationsmentioning
confidence: 77%
“…[4] Eine aktuelle Veröffentlichung trägt den Titel "Resonant Tunneling Processes along Conjugated Molecular Wires: A Quantum-Chemical Description". [5] Bré das ist Träger zahlreicher Auszeichnungen und war 1997 -1999 Präsident der Socié té Royale de Chimie, der chemischen Gesellschaft des französischsprachigen Teils Belgiens. Er ist Mitglied der Beiräte des European Journal of Inorganic Chemistry und von Advanced Functional Materials.…”
unclassified